Strategi Pengembangan Bisnis Laundry Berbasis Online - Asro; Istiharoh, Iis (Amal Insani Foundation, 2023)
In the modern digital era, technology and social media are crucial in supporting businesses, including the laundry business. This business falls under the category of Micro, Small, and Medium Enterprises (MSMEs) that operate in the service sector. Xilaundry, located in Serang Regency, Banten Province, exemplifies how MSMEs utilize technology in their operations. Xilaundry uses social media platforms such as WhatsApp, Instagram, and Facebook for marketing and promotional strategies. Two payment methods are available for customers: conventional (pay on the spot) and digital (ATM, mobile banking, OVO, and Gopay). Xilaundry implements a SWOT analysis for its business strategy development. The results show that Xilaundry's business is feasible to run. Xilaundry's finances record a monthly turnover of IDR 6,570,800 and a cash expenditure of IDR 2,890,000. This generates a net profit of around IDR 2,743,800 per month. Thus, Xilaundry can generate a net income of approximately IDR 34,680,000 in a year. In the SWOT and social media context, Xilaundry can leverage its strength in using social media for marketing and promotion (strength). However, they must maintain service quality to avoid weaknesses in service (weakness). The opportunity that Xilaundry can take is the increase in social media and digital payment users (opportunity), while threats can come from competitors who also use social media in their marketing strategies (threat).